MOOCs in Sports Learning : A Literature Review - Widiawati, Prisca; Hanief, Yulingga Nanda; Supriantna, Supriatna (Physical Education, Health and Recreation Study Program, Universitas Insan Budi Utomo, Indonesia, 2023)
The purpose of this article is to present a review of published journal content from several research results focused on MOOC in sports learning. The research method used is literature review using the Google Scholar and Eric databases. With the keywords MOOC and Physical Activity, MOOC and Sport Education. The articles analyzed were published from 2017 to 2022, using the following inclusion criteria: international journals, articles of at least the last 6 years, the research sample is students. There are 10 articles reviewed from international journals. The results of the 10 articles reviewed show that MOOC improves classroom learning efficiency, creates an active and open learning atmosphere, creates a relaxed and lively teaching environment, and realizes diverse teaching styles not only increasing student enthusiasm and interest, but also providing learning creative. The conclusions of the 10 articles reviewed show that MOOC can improve the quality of learning in physical education.